2015
DOI: 10.1155/2015/762546
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Antral Vascular Ectasia in Systemic Sclerosis: Current Concepts

Abstract: Introduction. Gastric antral vascular ectasia (GAVE) is a rare entity with unique endoscopic appearance described as “watermelon stomach.” It has been associated with systemic sclerosis but the pathophysiological changes leading to GAVE have not been explained and still remain uncertain. Methods. Databases Medline, Scopus, Embase, PubMed, and Cochrane were searched for relevant papers. The main search words were “Gastric antral vascular ectasia,” “Watermelon Stomach,” “GAVE,” “Scleroderma,” and “Systemic Scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…GAVE has been well described in patients with systemic sclerosis/scleroderma with an estimated prevalence of 5.7% in this population [ 18 ]. In fact, some studies suggest that this number may be substantially higher considering asymptomatic patients with endoscopic findings of GAVE.…”
Section: Discussionmentioning
confidence: 99%
“…GAVE has been well described in patients with systemic sclerosis/scleroderma with an estimated prevalence of 5.7% in this population [ 18 ]. In fact, some studies suggest that this number may be substantially higher considering asymptomatic patients with endoscopic findings of GAVE.…”
Section: Discussionmentioning
confidence: 99%
“…GAVE is part of the spectrum of vascular disease in these patients[ 16 , 24 ]. The prevalence is variable, with reports between 1%-76%[ 85 ]. A study that evaluated abnormalities of the GI mucosa by video capsule endoscopy found “watermelon stomach” (34.6%), gastric and/or SB telangiectasia (26.9%), and gastric and/or SB angiodysplasia (38.5%).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…GAVE can present with asymptomatic or symptomatic iron deficiency anemia (weakness, fatigue, or dyspnea), occult blood in the stool, and overt bleeding due to melena or hematemesis[ 14 , 85 ]. Endoscopically, the typical "watermelon stomach" is found with prominent, flat, or raised erythematous stripes that radiate from the antrum with a tendency to converge towards the pylorus, the finding of which is the most frequent, and the “honeycomb stomach”, where vascular ectasia appears as a coalescence of multiple round angiodysplasias in the antrum[ 88 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations